Psychological Factors Influencing Leadership, Diversity and Equality for Better Inclusive Education Practices - Almanfaluthi, Muhammad Luthfi; Noval, Sayid Muhammad Rifki; Ghoer, Hilman Farouq (International Journal of Membrane Science and Technology, 2023)
To promote inclusive practices holistically within Indonesia’s school system, three ideas–leadership, diversity, and equality–have been constructed and integrated within the operationalization of the inclusive education concept. This study has been carried out to understand the influence of leadership, diversity, and equality factors on inclusive practices in schools, especially in Indonesia. This study used a correlational research method with a questionnaire as the data collection technique. Questionnaires were distributed to 212 respondents living in West Java Province, Indonesia. The research was based on the theory of inclusion, equality, diversity, and leadership in teaching and learning. The data analysis, using multivariate analysis of variance (MANOVA), revealed that female teachers had good knowledge and were found to be prospective teachers with better support for inclusive education. However, it has been established that variations exist regarding the way special education teachers and general teachers address practical leadership, diversity, and equality in an inclusive learning environment. Experienced teachers, in support of inclusive practices within education, were observed to understand their leadership style, perceptions regarding the equality of learners, and how they handle students’ diversity within a school enclosure. It has been concluded that the attitudes of both experienced and inexperienced teachers toward leadership, equality, and diversity influence the promotion of inclusive practices.